PENYULUHAN PENTINGNYA ASI EKSKLUSIF DI POSYANDU MAWAR PEKON SIDOMULYO WILAYAH KERJA PUSKESMAS PAGAR DEWA LAMPUNG BARAT TAHUN 2017 - Aryanti Wardiyah; Riska Wandini; Suryani Suryani (Universitas Malahayati Lampung, 2018)
ABSTRACTThe most important nutritional problem in Indonesia is less calories and protein. It is commonly found in infants and children. Various reasons on mothers who misunderstanding about exclusive breastfeeding to their babies, including the production , the desire to be modern mother and the influence of substitute advertising milk and the assumption that everyone already has knowledge about breastfeeding. The purpose of the activity is expected to be able to understand about the importance of exclusive breastfeeding in babies. This activity was carried out on Friday, December 15, 2017. The activities carried out in the form of counseling to mothers about the importance of exclusive Breastfeeding in Posyandu Mawar Pekon Sidomulyo Lampung Barat using leaflets. There was a significant influence on mother's knowledge before and after exclusive counseling. Thus, the provision of education can provide increased knowledge, particularly those related to exclusive breastfeeding. Keywords: Exclusive Breastfeeding, Level of Knowledge, Counseling